1998
DOI: 10.1097/00005537-199811000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Balanced orbital decompression for graves' ophthalmopathy

Abstract: The endoscopic approach to the medial orbital wall is an important component of balanced orbital decompression for patients with Graves' ophthalmopathy. Balancing the decompression and preserving the medial orbital strut between the ethmoid cavity and the orbital floor may minimize the risk of diplopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 25 publications
3
61
0
Order By: Relevance
“…11,22 As techniques for orbital decompression have advanced, the minimal morbidity from surgery has meant that an increasing number of patients are now requesting intervention for purely cosmetic reasons. 1,23,24 In this series and others endoscopic decompression of the medial orbital wall and oor gives reasonable proptosis reduction with minimal morbidity and, therefore, should be considered as a treatment option.…”
mentioning
confidence: 59%
“…11,22 As techniques for orbital decompression have advanced, the minimal morbidity from surgery has meant that an increasing number of patients are now requesting intervention for purely cosmetic reasons. 1,23,24 In this series and others endoscopic decompression of the medial orbital wall and oor gives reasonable proptosis reduction with minimal morbidity and, therefore, should be considered as a treatment option.…”
mentioning
confidence: 59%
“…This technique was reported to be associated with a greater reduction of proptosis and lower prevalence of postoperative diplopia compared with the transantral technique (138). It was observed that balancing the decompression and preserving the medial orbital strut between the ethmoid sinus and the orbital floor may minimize the risk of postoperative diplopia (144). In a large, retrospective study (138), the mean decrease in proptosis was 4.3 mm (range 0 -10 mm), the largest reduction being observed in those patients who had the highest (Ͼ27 mm) preoperative Hertel readings.…”
Section: Orbital Decompressionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The mainstay of treatment has been two wall decompression originally described by Walsh and Ogura 4 in 1957, modified into an endoscopic formulation by Kennedy in 1990. 7 Although inferomedial orbital decompression has afforded good results in terms of proptosis reduction, it accrues a large risk of postoperative diplopia, with rates of postoperative motility imbalance as high as 80%.…”
Section: Introductionmentioning
confidence: 99%
“…8 In fact, even with the creation of a strut at the ethmoid-maxillary junction, two wall decompression still carries such a high risk of postoperative diplopia 9,10 that some surgeons do not even consider it to be a complication. 11 Alternative techniques have been sought in an attempt to decrease decompression-induced diplopia; 1 Graham et al 12 suggested a balanced decompression that requires lateralization of the outfractured lateral wall, whereas the lateral orbital wall has recently been suggested as the region of first choice for orbital decompression as it provides a low risk of consecutive diplopia or severe complications, such as cerebrospinal fluid leak. 13 Despite the wide variety of innovative approaches designed by multidisciplinary teams, orbital decompression remains a technically challenging procedure where the goal of proptosis reduction competes with postoperative diplopia and cosmetic requests of an increasingly demanding patient population.…”
Section: Introductionmentioning
confidence: 99%